8‐Benzyltetrahydropyrazino[2, 1‐f]purinediones: Water‐Soluble Tricyclic Xanthine Derivatives as Multitarget Drugs for Neurodegenerative Diseases. Issue 8 (9th May 2014) - Brunschweiger, Andreas; Koch, Pierre; Schlenk, Miriam; Pineda, Felipe; Küppers, Petra; Hinz, Sonja; Köse, Meryem; Ullrich, Stefan; Hockemeyer, Jörg; Wiese, Michael; Heer, Jag; Müller, Christa E.
Abstract 8‐Benzyl‐substituted tetrahydropyrazino[2, 1‐f]purinediones were designed as tricyclic xanthine derivatives containing a basic nitrogen atom in the tetrahydropyrazine ring to improve water solubility. A library of 69 derivatives was prepared and evaluated in radioligand binding studies at adenosine receptor (AR) subtypes and for their ability to inhibit monoamine oxidases (MAO). Potent dual‐target‐directed A1/A2A adenosine receptor antagonists were identified. Several compounds showed triple‐target inhibition; one of the best compounds was 8‐(2, 4‐dichloro‐5‐fluorobenzyl)‐1, 3‐dimethyl‐6, 7, 8, 9‐tetrahydropyrazino[2, 1‐f]purine‐2, 4(1H, 3H)‐dione (72) (human AR: Ki A1 217 nM, A2A 233 nM; IC50 MAO‐B: 508 nM). Dichlorinated compound 36 [8‐(3, 4‐dichlorobenzyl)‐1, 3‐dimethyl‐6, 7, 8, 9‐tetrahydropyrazino[2, 1‐f]purine‐2, 4(1H, 3H)‐dione] was found to be the best triple‐target drug in rat (Ki A1 351 nM, A2A 322 nm; IC50 MAO‐B: 260 nM), and may serve as a useful tool for preclinical proof‐of‐principle studies. Compounds that act at multiple targets relevant for symptomatic as well as disease‐modifying treatment of neurodegenerative diseases are expected to show advantages over single‐target therapeutics.